Critique of the internalism/ externalism approach as a way of extending the synthetic theory - Dressino, Vicente (2011)
For around 150 years, Darwinism and the modern synthesis have endured as theoretical approaches in the field of evolutionary biology. Over this period, biologists have made unprecedented progress as regards to their concepts, methods and instruments. By way of example, when Darwin postulated his theory on the origin of species, it was not yet possible to see a chromosome, much less to see how it worked during the different stages of the cell division. Strikingly, the modern synthesis has generated a set of hypotheses that keep the core of Darwinian theory intact, as put forward in Marta Linde Medina’s (2010) interesting target article.